Pengembangan Sistem Informasi Penyambungan Baru Listrik Khusus Pelanggan Getting Electricity Berbasis Web Pada PT.PLN (Persero) Distribusi Jawa Timur Area Gresik - Mahda Dina Alam Rusbandi; Ismiarta Aknuranda; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PLN (Persero) East Java distribution Gresik area was a company located in an industrial area, offering services to customers where most of the customers were business and industrial customers who had a medium voltage which is 100-200 kVA is called getting electricity customers. But there were still some obstacles in serving new electrical connections, which was the Customer Service Division must ask each division in charge to know the progress of the electricity installation process. To answer this problem, business process modeling, requirements analysis, design and implementation were carried out by applying an object-oriented approach in the New Electricity Installation Information System. After that, the results of the system implementation were tested to find out if the system could run according to the requirements that had been identified. Business process modeling produced As-Is business process models and To-Be business processes, requirements analysis with 28 functional requirements and 1 non-functional requirement, as well as visualizing the system's capabilities in a use case diagram. The results of the system design were models of object interactions in sequence diagrams, object models in class diagrams, database design, algorithm design, and interface design. The result of the implementation was a web-based New Electricity Installation Information System tested with 3 blackbox tests, which were browser compatibility testing, display responitivity testing, and validation testing.